Sustainable Innovation And Competitive Advantage In Improving The Marketing Performance Of Waste-Base Sculpture In Bali - Pande Ketut Ribek (Institut Seni Indonesia Denpasar, 2021)
To increase competitive advantage, all companies have unique strategies to improve their marketing performance. Competition is very competitive in this digital era, making management to motivate themselves and business people to always maximize service to their customers in order to remain loyal customers. Likewise, the business in the art of sculpture made from stone waste which will be traded to be able to increase its superiority in a sustainable manner. The excellence or strength of the sculpture business is able to produce creative and innovative products in the form of ideas and ideas in creating new products. To win the competition, a company must always be creative and innovative so that it is able to meet consumer needs according to changing tastes and times. There is fore a marketing strategy model is needed that is in accordance with the company’s conditions with sustainable innovation so that in the future it is hoped that the sculpture business made from waste rock can be more developed and the company’s goals can be achieved both short too long term goals. This study aims to determine the indicators used in increasing competitive advantage so as to improve marketing performance. The population in this study amounted to 100 sculpture businesses and used saturated samples. The analytical tool used in this research is Smart PLS. 3.0. The findings of this study are that sustainable innovation is able to increase competitive advantage in stone-waste sculpture businesses, Sustainable innovation is not able to increase direct marketing performance, Sustainable innovation is able to improve marketing performance mediated by competitive advantage. The limitation of this research is that this research only examines the art of sculpture made from stone waste found in Bali, so it is not able to generalize. The recommendation in this study is that future researchers are expected to investigate other business fields with a larger number of samples.